Analisis Kemampuan Berbicara Melalui Metode Bercerita pada Materi Teks Hikayat Peserta Didik Kelas X SMK Negeri 1 Palembang - Ayu Puspita Indah Sari; Fisca Dinda Ayurizky (Universitas Pancasakti Tegal, 2023)
The use of the storytelling method in learning can motivate and provide opportunities to express thoughts and opinions in oral form when practicing retelling. This study aims to describe the ability to speak through the method of storytelling in the text of the saga text of class X Tiket SMK 1 Palembang. The results of this study indicate that the indicators for assessing speaking ability in class X TJKT 1 SMK 1 Palembang students include the sentence structure indicator getting the highest score with a percentage of 20%. Indicators of low ability assessment on the speaking ability of class X TJKT 1 students are performance indicators. The distribution of speaking ability found in the performance appraisal indicator is 7%. The pronunciation indicator is 18%, the paralanguage indicator is 19%, and the story content indicator is 17%. The main factor causing the inability to speak in class X TJKT 1 students at SMK Negeri 1 Palembang is a lack of confidence. Students who lack confidence when carrying out a speaking ability test will look nervous, uneasy, anxious, giving rise to flat expressions or not in accordance with the story being told. Confidence in learning speaking skills includes speaking attitudes and courage.